Detection of non-halal dog leather and dog leather products - Mirghani, Mohamed Elwathig Saeed; Gasmelsid, Saadeldin Mansour (2012)
This study consists of two parts; the first part is about dog leather whether it is halal or non-halal according to Islamic Shri’a and explanation by Islamic scholars. The second part is about how to detect dog leather and its products using scanning electron microscope (SEM) and Fourier Transform Infrared (FTIR) spectroscopy. In the 1st part and according to many Islamic scholars only pig and dog leathers are not permissible to be processed for Muslim use. For the second part ESM was used successfully to differentiate between dog leather and other halal leather such as sheep, goat and cow ones. Also FTIR spectroscopy showed differences in peaks at the spectral regions 1709, 1403, 1030, 878 and 591 cm–1 for non-halal dog leather and others halal leathers in both raw and processed types of leathers. The results showed rapid, reliable and convenient qualitative detection of non halal leather and its products using FTIR spectroscopy as well as SEM.